ANALYSIS OF FINANCIAL ASSISTANCE FROM INTERNATIONAL FINANCIAL INSTITUTIONS OF MOLDOVA - Stupachev, Sergey (Economy and Sociology, 2022)
The article considers the financial assistance of international financial institutions (the International Monetary Fund and the World Bank) to the Republic of Moldova in their partnership process. The relevance of the study is determined by the objective need to use this financial assistance to solve urgent financial and economic problems and implement an effective economic policy of Moldova. The purpose of the article is to analyze the financial assistance of International Financial Institutions to Moldova, to assess the current state and prospects for developing their financial relations. The information base of the research consists of theoretical and methodological scientific studies of foreign and Moldovan economists devoted to the subject under consideration; information materials of official websites of financial organizations. It is shown that for the entire period of financial support of Moldova by the International Monetary Fund, almost all special credit mechanisms have been implemented. Since 1993, the World Bank has been implementing and financing 118 different projects (90 completed, 18 active and 7 under development). Agriculture accounts for the largest number of projects financed by the bank. It is revealed that the country's debt and overdue obligations to International Financial Institutions have an upward trend, which is due to the crises and financial instability of 2008 and 2019. The continuation of such a trend in the future may lead to certain financial and economic problems if the financial assistance received does not lead to significant development of the Moldovan economy.